PHILOSOPHICAL UNDERPINNINGS OF GROWTH MINDSET INTERVENTION - Prawitasari, Galuh; Sugiharto, Dwi Yuwono Puji; Mulawarman, Mulawarman (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
The concept of growth mindset has gained widespread attention in educational discourse as a tool to enhance students’ motivation, well-being, and academic success. However, the implementation of growth mindset interventions often emphasizes behavioral outcomes while neglecting the deeper philosophical foundations that shape students' sense of self, purpose, and well-being. This paper presents the ontological, epistemological, and axiological domains of growth mindset interventions by reviewing the primary and secondary relevant literatures. A thorough examination of these philosophical dimensions enables practitioners to more effectively integrate the principles of growth mindset interventions into their professional practice.